If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-1b + 2 + 7 + -1) = 13 + 3b + 5b Reorder the terms: 7(2 + 7 + -1 + -1b) = 13 + 3b + 5b Combine like terms: 2 + 7 = 9 7(9 + -1 + -1b) = 13 + 3b + 5b Combine like terms: 9 + -1 = 8 7(8 + -1b) = 13 + 3b + 5b (8 * 7 + -1b * 7) = 13 + 3b + 5b (56 + -7b) = 13 + 3b + 5b Combine like terms: 3b + 5b = 8b 56 + -7b = 13 + 8b Solving 56 + -7b = 13 + 8b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-8b' to each side of the equation. 56 + -7b + -8b = 13 + 8b + -8b Combine like terms: -7b + -8b = -15b 56 + -15b = 13 + 8b + -8b Combine like terms: 8b + -8b = 0 56 + -15b = 13 + 0 56 + -15b = 13 Add '-56' to each side of the equation. 56 + -56 + -15b = 13 + -56 Combine like terms: 56 + -56 = 0 0 + -15b = 13 + -56 -15b = 13 + -56 Combine like terms: 13 + -56 = -43 -15b = -43 Divide each side by '-15'. b = 2.866666667 Simplifying b = 2.866666667
| 15b-9=51 | | X(x^2+3)=6+x^3 | | 25x+5x+25+10x-90= | | 1.5(2x+2)=6 | | .05x+.12x=.85 | | 2a+2/3=a-1/3 | | 4(x+2)=58+3x | | -38=13a+1 | | 285-6x=39x+20 | | f=-4+6x | | f=-3+4x-1+2x | | -8-9x=138-44x | | 6y+-4(y-2)+4= | | 2*w+3=24 | | (8-3*2)2= | | 8-9x=138-44x | | 7x-29=55 | | 4+15r=100 | | 3a+18a= | | 46=10r-14 | | -4x-4x=67-3 | | 0.20x+0.35(70)=32.5 | | 52s+30=12s | | 2c-2=-6 | | -2x^2-2=0 | | -129.5=15a-11 | | 3x(x-2)+5=3+x(2+3x) | | -6+5x=-18+4x | | 3x+3=x+-3 | | -281=19-15t | | -281=19-15t | | (x^2)-8x-3=0 |